SPS30 and SEN55 PM2.5 sensor intercomparison and validation through indoor and outdoor measurements in Arba Minch, Ethiopia - Dingemanse, Johannes Dirk ; 0000-0003-3489-0374; Kimo, Israel Gebresilasie; Ibrahim, Awel Haji; Demeke, Yared Godine; Kalbe, Nazrawit Samuel; Isaxon, Christina; Eriksson, Axel C. ; 0000-0002-1692-0376 (Preprint egusphere, 2026)
Ethiopian air pollution is understudied yet highly relevant considering population size and source abundance including solid fuel cooking, small scale waste burning and vehicle fleet. Low cost PM2.5 sensors can be used to mitigate this by mapping pollution exposure. We report on indoor and outdoor measurements with Sensirion sensors SPS30 and SEN55, the former extensively validated in literature, the latter not. We evaluate their use in Arba Minch, population ca 200.000. In addition to sensor inter and intra comparison we benchmark the low-cost sensors against gravimetry. Furthermore, a separate Swedish outdoor dataset is included to extend the range of particle types and loadings and evaluate relative humidity (RH) effects using a reference-equivalent monitor (Palas FIDAS). We found that the SEN55 consistently reports values 6–10 % higher than the SPS30; once this systematic offset is corrected, the sensor types are functionally identical with high precision (coefficient of variation ≤ 7.7 %, between-sampler uncertainty ≤ 1.7 µg m-3). Both sensors demonstrated high stability across repeated high-concentration events (> 1000 µg m-3). While the SEN55 exhibits digital truncation at 6553.4 µg m-3, we find that measurements beyond the 1000 µg m-3 manufacturer specification remain meaningful and essential for accurate mass estimation in biomass-burning environments. The impact of relative humidity was small and consistent across both sensor types. Our study shows that the SPS30 and SEN55 – when calibrated under circumstances of use – are stable and accurate instruments (indoor and outdoor accuracy error ≤ 22 %, outdoor expanded uncertainty ≤ 15 % in comparison to gravimetric measurements). Pragmatic, large-scale low-cost monitoring supported by mobile gravimetric validation offers the most viable path toward mitigating air pollution exposure in resource-constrained settings.
This preprint is open for discussion and under review for Atmospheric Measurement Techniques (AMT) - ISSN (Print): 1867-8548.
Keywords: Low-cost sensors; Biomass burning; Gravimetry; Digital truncation; Sub-Saharan Africa; Resource-limited settings